CSF concentration gradients of monoamine metabolites in patients with hydrocephalus. Issue 9 (September 1994) - Malm, J; Kristensen, B; Ekstedt, J; Wester, P
Abstract : Concentration gradients of homovanillic acid (HVA), 5-hydroxyindoleacetic acid (5-HIAA), and 3-methoxy-4-hydroxyphenylglycol (MHPG), were assessed in 762 successive CSF fractions (2 ml lumbar CSF) from 15 patients with the adult hydrocephalus syndrome (AHS) and 11 patients with hydrocephalus of other causes (mixed group). A mean volume of 49.6 (SD 11.8) ml CSF was removed in the AHS group and 56.4 (10.2) ml in the mixed group. The CSF was collected with a specially designed carousel fraction collector and the corresponding CSF dynamics were continuously registered by a constant pressure CSF infusion method. Pronounced gradients in CSF HVA and CSF 5-HIAA were seen in both patient groups in the first 25 ml of CSF removed. The concentration curves levelled off, despite the removal of larger amounts of CSF and stabilised at about twice the initial concentrations. This phenomenon has not been described before. Concentrations of HVA and 5-HIAA in the first CSF fraction correlated strongly with concentrations in fractions up to about 40 ml. A positive correlation between the first fraction of CSF HVA and CSF 5-HIAA concentrations and CSF outflow conductance was found in the AHS group. There was no gradient in MHPG. It is suggested that the rostrocaudal gradients in CSF HVA and 5-HIAA may be explained by a downward flow of CSF along the spinal cord with absorption of metabolites occurring during passage. Mixing of CSF from different CSF compartments, extraventricular production sites of CSF, clearance of metabolites to venous blood or extracellular fluid, and CSF outflow conductance are probably important determinants of the plateau phase in patients with hydrocephalus. It is concluded that lumbar CSF does not exclusively reflect the concentrations of HVA, 5-HIAA, or MHPG in the ventricles. It should be noted that these results obtained in patients with hydrocephalus may not be applicable to other groups of patients or normal subjects.